Gut microbiota-derived indole-3-propionic acid alleviates diabetic kidney disease through its mitochondrial protective effect via reducing ubiquitination mediated-degradation of SIRT1 - Yan Zeng; Man Guo; Qi Wu; Xiaozhen Tan; Chunxia Jiang; Fangyuan Teng; Jiao Chen; Fanjie Zhang; Xiumei Ma; Xinyue Li; Junling Gu; Wei Huang; et al. (Journal of Advanced Research)
Introduction: Gut microbes and their metabolites play crucial roles in the pathogenesis of diabetic kidney disease (DKD). However, which one and how specific gut-derived metabolites affect the progression of DKD remain largely unknown. Objectives: This study aimed to investigate the potential roles of indole-3-propionic acid (IPA), a microbial metabolite of tryptophan, in DKD. Methods: Metagenomic sequencing was performed to analyze the microbiome structure in DKD. Metabolomics screening and validation were conducted to identify characteristic metabolites associated with DKD. The protective effect of IPA on DKD glomerular endothelial cells (GECs) was assessed through in vivo and in vitro experiments. Further validation via western blot, immunoprecipitation, gene knockout, and site-directed mutation elucidated the mechanism of IPA on mitochondrial injury. Results: Alterations in gut microbial community structure and dysregulated tryptophan metabolism were evident in DKD mice. Serum IPA levels were significantly reduced in DKD patients and correlated with fasting blood glucose, HbA1c, urine albumin-to-creatinine ratio (UACR), and estimated glomerular filtration rate (eGFR). IPA supplementation ameliorated albuminuria, bolstered the integrity of the glomerular filtration barrier, and mitigated mitochondrial impairments in GECs. Mechanistically, IPA hindered SIRT1 phosphorylation-mediated ubiquitin–proteasome degradation, restoring SIRT1′s role in promoting PGC-1α deacetylation and nuclear translocation, thereby upregulating genes associated with mitochondrial biosynthesis and antioxidant defense. Conclusion: Our findings underscore the potential of the microbial metabolite IPA to attenuate DKD progression, offering novel insights and potential therapeutic strategies for its management.